Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1083/jcb.151.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Reconstitution of Microautophagic Vacuole Invagination and Vesicle Formation

Abstract: Many organelles change their shape in the course of the cell cycle or in response to environmental conditions. Lysosomes undergo drastic changes of shape during microautophagocytosis, which include the invagination of their boundary membrane and the subsequent scission of vesicles into the lumen of the organelle. The mechanism driving these structural changes is enigmatic. We have begun to analyze this process by reconstituting microautophagocytosis in a cell-free system. Isolated yeast vacuoles took up fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 53 publications
(82 reference statements)
4
95
0
1
Order By: Relevance
“…That observation supports our analysis that fails to detect any t-SNARE at the PAS (Figure 2, D and E), and it suggests a different mechanism takes place during double-membrane vesicle sealing. This suggestion would be in agreement with the finding that microautophagy, another process that requires the fusion of double membranes, does not use the SNARE proteins involved in homotypic vacuole fusion (Sattler and Mayer, 2000); that is, a different type of fusion event is taking place that is independent of SNAREs.…”
Section: The Pas and Double-membrane Vesicle Biogenesis Depends On Easupporting
confidence: 77%
See 1 more Smart Citation
“…That observation supports our analysis that fails to detect any t-SNARE at the PAS (Figure 2, D and E), and it suggests a different mechanism takes place during double-membrane vesicle sealing. This suggestion would be in agreement with the finding that microautophagy, another process that requires the fusion of double membranes, does not use the SNARE proteins involved in homotypic vacuole fusion (Sattler and Mayer, 2000); that is, a different type of fusion event is taking place that is independent of SNAREs.…”
Section: The Pas and Double-membrane Vesicle Biogenesis Depends On Easupporting
confidence: 77%
“…That observation supports our analysis that fails to detect any t-SNARE at the PAS (Figure 2, D and E), and it suggests a different mechanism takes place during double-membrane vesicle sealing. This suggestion would be in agreement with the finding that microautophagy, another process that requires the fusion of double membranes, does not use the SNARE proteins involved in homotypic vacuole fusion (Sattler and Mayer, 2000); that is, a different type of fusion event is taking place that is independent of SNAREs.Previous studies have shown that part of the machinery involved in COPII vesicle formation is also required for autophagy but not the Cvt pathway (Klionsky et al, 1992;Ishihara et al, 2001). One problem is that those studies used conditional alleles, and it is not clear how long it takes to interfere with either the preexisting or the forming PAS after the block is induced by the temperature shift.…”
supporting
confidence: 77%
“…The process has been studied mainly in yeast and cell free systems, and little is known about the molecular mechanism of microautophagy in mammals 147,148 . It is generally accepted that microautophagy is a constitutively active, nonselective catabolic pathway in the cell.…”
Section: Autophagy As An Endogenous Antigen Loading Pathwaymentioning
confidence: 99%
“…Fusion of the outer autophagosomal layer with the vacuolar membrane liberates autophagic bodies (single-layered intravacuolar vesicles) into the vacuolar lumen for degradation (Takeshige et al, 1992). Relevant actors of macroautophagy (Atg proteins; Klionsky et al, 2003) have been identified, mainly by genetic screens (Tsukada and Ohsumi, 1993;Thumm et al, 1994;Harding et al, 1995Harding et al, , 1996Titorenko et al, 1995) and have been studied intensively over the last decade.Little is known about microautophagy, a process consisting of a direct invagination of the vacuolar boundary membrane and budding of autophagic bodies into the vacuolar lumen (Muller et al, 2000;Sattler and Mayer, 2000;Kunz et al, 2004). Microautophagy of soluble cytosolic components is topologically equivalent to invaginations occurring during multivesicular body (MVB) formation at the endosome, piecemeal microautophagy of the nucleus (PMN) (Roberts et al, 2003) into the yeast vacuole and micropexophagy in methylotrophic yeasts (Veenhuis et al, 1983;Tuttle et al, 1993;Tuttle and Dunn, 1995;Sakai et al, 1998;Mukaiyama et al, 2002Mukaiyama et al, , 2004.…”
mentioning
confidence: 99%
“…Also nascent autophagosomes are virtually free of intramembraneous particles, suggesting that membrane removal by microautophagy might compensate macroautophagic membrane influx both in terms of quantity and quality. Microautophagic vacuole invagination could be reconstituted in a cell-free system composed of purified vacuoles and cytosolic extracts (Muller et al, 2000;Sattler and Mayer, 2000). Using a pharmacological approach, the in vitro uptake reaction could be dissected into different kinetic stages (Kunz et al, 2004).…”
mentioning
confidence: 99%